Influence of process parameters on surface integrity during EDM of mild steel - Khan, Ahsan Ali; Adesta, Erry Yulian Triblas; Mohammad , Yeakub Ali (2010)
The present paper reports on the influence of process parameters on surface quality of mild steel during EDM using a copper electrode. Surface quality was evaluated on the basis of work surface roughness, micro cracks and thickness of the recast layer. Current, pulse-on time, pulse-off time and voltage were the variable parameters for the present investigation. It was found that pulse-on time is the most significant factor for work surface roughness. With increase in pulse-on time the work material gets more time to absorb heat and more melting and vaporization of material takes place producing a rough surface. Work surface roughness was also found to increase with increase in current. A higher current produces a spark of higher energy removing more material and leaving a larger crater that results a rough surface. An increase in voltage also results a poorer surface, but voltage demonstrated to have a very small effect on job surface roughness. Micro cracks were found on the surface due to rapid heating and cooling of the surface during EDM. Micro cracks reduced in number and size when the surface was EDMed with a low current and a short pulse-on time. A layer of recast layer on the work surface was observed after EDM. The thickness of the recast layer was higher while a higher current together with a higher pulse-on time were used. It was concluded that in order to have a high quality surface it should be machined with lower values of current, pulse-on time and voltage.